Author correction: Emissive spin-0 triplet-pairs are a direct product of triplet-triplet annihilation in pentacene single crystals and anthradithiophene films - Bossanyi, David G.; Matthiesen, Maik; Wang, Shuangqing; Smith, Joel; Kilbride, Rachel C.; Shipp, James D.; Chekulaev, Dimitri; Holland, Emma; Anthony, John E.; Zaumseil, Jana; Musser, Andrew J.; Clark, Jenny (Nature chemistry, 2023)
A Correction to this paper has been published: https://doi.org/10.1038/s41557-020-00622-w
Gesehen am 18.12.2023